Estudio del rendimiento a la canal en cabras faenadas en el camal municipal del cantón Zapotillo - Salazar Jiménez, Nathaly Viviana (2024)
In southern Ecuador, especially within the seasonal dry forest ecosystem, over 70% of the country's goat population is found. These goats are managed in open fields with minimal technological input. This study aimed to assess their performance concerning hot and cold carcass yields and the degree of runoff. A total of 457 goats: 302 males and 155 females, of various ages, genetic backgrounds, and biotypes were analyzed post-slaughter at the Municipal Slaughter Center of Zapotillo Canton. Data collected included ante-mortem weights and both hot and cold carcass weights. Factors such as sex, age, breed group, origin, and biotype were evaluated using ANOVA with a randomized linear model. The goats exhibited hot and cold carcass yields of 41.8 ± 2.6% and 41.1 ± 2.7%, respectively, with a runoff degree of 1.23%. No statistically significant differences were observed among the factors analyzed (P > 0.05). A slight decline in carcass yield with age was noted: goats under 4 years had a yield of 41.9%, while those over 4 years had a yield of 41.3%. Males displayed a marginally higher carcass yield (41.9%) compared to females (41.7%). Minor variations in carcass yield were observed among breed groups, with Chuscos Criollos 70% of slaughtered animals at 41.8%, Mestizos (23%) at 42%, and Anglo Nubians (7%) at 41.7%. Carcass yields also varied by origin, with goats from Limones, Zapotillo, and Garza Real yielding 41.8%, 41.9%, and 41.7%, respectively. Additionally, carcasses were categorized by biotype and horn presence, with horned goats yielding 41.8% and non-horned goats 41.9%. In conclusion, this goat population demonstrates lower carcass yields compared to other populations but is notable for its minimal runoff, likely due to specific management and feeding practices, especially the limited availability of water. The observed slight advantage in mestizo goats suggests their potential as a viable option for improving these performance metrics.